An integrated inflammatory and metabolic profiling of stromal-epithelial cell interactions in colorectal cancer - Ng, AS (2023)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer and ranks second as the leading cause of cancer deaths worldwide. Notably, it was predicted that a positive annual decline of 2 % in global incidence rates would eventually still lead to a rise in the projected burden of CRC. Therefore, it is pertinent to push the forefront of cancer treatments to reduce the predicted increase in the future CRC incidence and mortality burden.